Research on Administrative Legislation of Personal Information Protection in Big Data Environment - Ming Gao (Design Engineering, 2021)
From the world to China, the upsurge of big data is constantly sweeping. This paper studies the administrative legislation of personal information protection in the big data environment. Because of the advantages of administrative organs, it is easier to become the subject of infringement. Compared with other subjects of private rights, the infringement of citizens' personal information by administrative organs is more worrying. This article is just for the consideration of maintaining the personal information security of citizens, using the knowledge of administrative law and combining with the content of personal information protection and its legislative mode in legal documents. Connecting with the reality of our country, this paper discusses how to choose the legislative mode and legal principles for the protection of personal information rights in the era of big data, how to make a breakthrough in the improvement of specific systems, and how to create a set of practical and effective protection norms in close connection with the current big data environment. In the theoretical introduction of the characteristics of big data and the right of personal information, this paper points out the risks and manifestations of the right of personal information. This paper proves the unique value of applying administrative law to protect this right. When discussing the drawbacks of the current legislation in our country, through the introduction of the legislative status of the two legal systems, this paper analyzes the reference value and the detours that need to be avoided, and analyzes the limitations, and finally comes to the countermeasures. In the face of information security, we can't sit back and be in a panic all day. We must strengthen the legislation, actively build the protection system, and finally realize the use and protection of personal information at the same time, and effectively protect the citizens' right to personal information.